The role of women in the management of Family Hope Program fund in Surabaya - Marhaeni Mega Wijayanti; Henny Rosalinda (Jurnal Sosiologi Dialektika, 2020)
This study examines the role of women in the utilization and management of the Family Hope Program fund and describes the process of gender relations constructed in beneficiary families in Surabaya. This qualitative study has two objectives, namely: (1) identifying the role of women in the utilization and management of Family Hope Program funds in Surabaya; and (2) describing the process of gender relations constructed in the beneficiary families. The results indicate that the role of women in managing Family Hope Program funds in Surabaya remains stagnant. Women benefiting from the fund plays a dual role of working in formal and informal sectors and carrying out domestic functions such as caring for babies, cooking, and the likes. These women do not carry out the role in managing the Family Hope Program fund as they are supposed to, such as managing finances and planning needs and spending. This indicates that men still dominate the role of determining the amount of allocation, whereas women are only executors. In addition, the Family Hope Program still cannot restructure the existing gender relations among the people of Surabaya. The program also does not change the pattern of gender relations in decision making in the household. This can be seen from family planning participation. Women benefiting from the fund are reluctant to use family planning contraception due to the husband’s prohibition.